Those Men and their Shackles. A Rare Discovery from Roman Dacia - Ana Cristina Hamat (Editura Mega, 2020)
In the collection of the Highland Banat Museum from Reșiţa, we can find a special artefact with the inventory number 34614, discovered in one of the Roman forts, from Banat region. It is a Roman shackle, found in the Roman fort of Vărădia Chilii, in 2006. From a typological point of view, the specimen found here, is certainly a shackle from the Roman period, which belongs to type 4 in W.H. Manning and to the type known as Kunzing in F. H. Thompson. It is part of a series of rather rare artefacts in the Empire, illustrated in Dacia by the discoveries made in the forts from Călugăreni, Buciumi, Ilișua, Mehadia and Bologa as well as in the research carried out in the military vicus from Porolissum, and also in the Ulpia Traiana Sarmizegetusa mithraeum. From the context, it is clear that the artifact was used by the military troops stationed here to secure prisoners of war or even non-submissive individuals from inside the military and can be dated to the beginning of the second century, between the conquest of Dacia and the years 117–118 AD. Furthermore, based on the fairly large inner diameter, it appears that the shackle found in Vărădia, fixed the feet and it is called fetter.